2021
DOI: 10.3389/fcell.2020.629397
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Mitochondrial Fission and Mitophagy Reciprocally Orchestrate Cardiac Fibroblasts Activation

Abstract: Although mitochondrial fission has been reported to increase proliferative capacity and collagen production, it can also contribute to mitochondrial impairment, which is detrimental to cell survival. The aim of the present study was to investigate the role of mitochondrial fission in cardiac fibroblasts (CF) activation and explore the mechanisms involved in the maintenance of mitochondrial health under this condition. For this, changes in the levels of mitochondrial fission/fusion-related proteins were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The effects of MFN2 and the alterations of MAMs in this process are certainly notwithstanding; the precise role of MAMs should be interpreted in caution, which could be confounded by mitochondrial dynamics. The enhanced MFN2 expression increased the mitochondrial fusion while reducing fission, and this has been reported to decrease glycolysis during the cardiac fibroblast activation (Gao et al, 2020). Previous studies found that HG-induced mitochondrial fission in various cell types, (Kobayashi et al, 2020;Wu Q. R. et al, 2021) and these may further support the MAM-independent effects in the study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The effects of MFN2 and the alterations of MAMs in this process are certainly notwithstanding; the precise role of MAMs should be interpreted in caution, which could be confounded by mitochondrial dynamics. The enhanced MFN2 expression increased the mitochondrial fusion while reducing fission, and this has been reported to decrease glycolysis during the cardiac fibroblast activation (Gao et al, 2020). Previous studies found that HG-induced mitochondrial fission in various cell types, (Kobayashi et al, 2020;Wu Q. R. et al, 2021) and these may further support the MAM-independent effects in the study.…”
Section: Discussionsupporting
confidence: 70%
“…Human ventricular CFs were purchased from the ScienCell Research Laboratories (ScienCell, CA, United States) and maintained according to the instructions and previous reports of the manufacturer (Gao et al, 2020;Tao et al, 2021). Briefly, cells were cultured in the complete medium containing basic medium (fibroblast medium, FM-2; ScienCell) and supplements (10% fetal bovine serum, Gibco, CA, United States; fibroblast growth supplement-2, diluted to ×1 according to the instruction of the manufacturer, ScienCell; and 1% penicillin/streptomycin, Gibco) in the incubator at 37 • C and 5% CO 2 .…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture, Plasmids, Transient Transfection, and Reporter Assay Primary cardiac fibroblasts were isolated and maintained in DMEM supplemented with 10% FBS as previously described (Gao et al, 2020;Liu et al, 2020;He et al, 2021;Zhao et al, 2021). Mouse embryonic fibroblasts (MEFs) were isolated and maintained in DMEM supplemented with 10% FBS as previously described (Angrisani et al, 2021).…”
Section: Animalsmentioning
confidence: 99%
“…Importantly, the interaction of tau with Drp1 is enhanced by tau phosphorylation and further reduces mitochondrial fission, promoting elongation of mitochondrial networks and consequently disrupting mitochondrial membrane potential ( Manczak and Reddy, 2012 ). Although loss of mitochondrial membrane potential is a trigger of mitophagy, tau-Drp1 interactions may blunt this process due to reduced mitochondrial fragmentation ( Shutt et al, 2011 ; Shirihai et al, 2015 ; Gao et al, 2021 ). Further exacerbating this, tau can sequester Parkin in the cytosol, preventing mitochondrial recruitment ( Hu et al, 2016 ; Cummins et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%